AKIBAT HUKUM BAGI PENANAM MODAL ASING YANG MELAKUKAN PELANGGARAN KONTRAK DALAM BERINVESTASI DI INDONESIA - Hendy Prabawa, Komang; -, Marwanto (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013, 2013)
Indonesia as a developing country, it requires substantial capital in implementing national development. Substantial capital needs was due to an effort to catch up with the development of the developed countries. The factors that influence economic development is the presence of Investment, both in the State Capital Investment and Foreign Investment. One of the legal means to resolve the problems that exist in Investing in violation of the contract, such as The Act Nomor 25, 2007 on Investment.
Keywords: Investment, Breach of Contract, Foreign Investment